Vitamin C Intake and Anti-Tuberculosis Drugs-Induced Hepatitis in Pulmonary Tuberculosis Patients - Rabbani, Hadiati; Nurwidya, Fariz; Andayani, Diyah Eka; Agustin, Heidy; Syam, Shaogi (Faculty of Medicine Universitas Airlangga, 2024)
Introduction: Drug-induced hepatitis (DIH) is one of the serious side effects of anti-tuberculosis drugs (ATD) that can reduce patient compliance with tuberculosis (TB) treatment, increase the risk of treatment failure, or develop drug resistance. Vitamin C is a potential antioxidant known to have a protective effect against DIH. This study examined the relationship between vitamin C intake and the incidence of ATD-induced hepatitis (ATDIH) in pulmonary TB patients at Persahabatan National Respiratory Referral Hospital, Jakarta. Methods: This was a cross-sectional study of 108 patients with drug-sensitive pulmonary TB. Data was collected using a sociodemographic questionnaire, anthropometric measurements, semi-quantitative food frequency questionnaire (SQ FFQ), and data on the subject's liver function laboratory results in the last 1 month. Fisher exact test was utilized to analyze the association between adequacy of vitamin C intake and DIH. Results: The proportion of DIH in pulmonary TB patients in this study was 6.5%. Most subjects were males (54.6%) with a median age of 41. The median vitamin C intake was 66.65 mg/day, with 63.0% of patients having an intake below the recommendation. Fisher's exact test showed that vitamin C intake was not statistically significantly associated with the incidence of ATDIH (OR 3.77 95% CI 0.44-32.55, p-value 0.256). No factors also influenced the incidence of ATDIH in this study. Conclusion: No association was found between vitamin C intake and other factors related to the incidence of ATDIH. This is the first study in Indonesia to link vitamin C and E intake with the incidence of DIH in drug-sensitive pulmonary TB patients, providing information for future studies.